2014
DOI: 10.2174/2210289201405020018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Alkaloid Compound and Antioxidant Activity of Rafflesia cantleyi and its Host, Tetrastigma tuberculatum

Abstract: Alkaloid compounds in Rafflesia cantleyi and host, Tetrastigma tuberculatum were identified using the phytochemical screening method and HPLC technique. The results showed positive test for the host, T. tuberculatum which indicates the presence of alkaloid whereas the screening test for R. cantleyi showed that alkaloid is absenced. Both extract were then subjected to HPLC for alkaloid identification and caffeine was used as standard. The spectroscopic data from HPLC revealed the presence of caffeine in both me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Several species of Rafflesia which has been studied previously also represents a good potential as antioxidant. Zulkffle et al (2014) stated that the Rafflesia cantleyi and host T. tuberculatum absorption of free radical activity is quite high with IC 50 value of 14.58 and 19.12 µg mLG 1 , as well as research and Puttipan and Okonogi (2014) on the Rafflesia kerri, which concludes the high antioxidant potential in the Rafflesia. Hossain et al (2011) stated that the flavonoids and terpenoids are potent antioxidants and the close relationship between the total phenolic content of the extracts with antioxidant activity.…”
Section: Papillosum (Bt1) Extract -----------------------------------mentioning
confidence: 93%
See 1 more Smart Citation
“…Several species of Rafflesia which has been studied previously also represents a good potential as antioxidant. Zulkffle et al (2014) stated that the Rafflesia cantleyi and host T. tuberculatum absorption of free radical activity is quite high with IC 50 value of 14.58 and 19.12 µg mLG 1 , as well as research and Puttipan and Okonogi (2014) on the Rafflesia kerri, which concludes the high antioxidant potential in the Rafflesia. Hossain et al (2011) stated that the flavonoids and terpenoids are potent antioxidants and the close relationship between the total phenolic content of the extracts with antioxidant activity.…”
Section: Papillosum (Bt1) Extract -----------------------------------mentioning
confidence: 93%
“…Research about bioprospecting of Rafflesia has been done in some country. Latest research about Rafflesia kerri carried by Puttipan and Okonogi (2014) while research about Rafflesia cantleyi and its host Tetrastigma tuberculatum carried by Zulkffle et al (2014). Both of this research found high antioxidant ability from their samples.…”
Section: Introductionmentioning
confidence: 90%
“…If with Mayer LP, a white or yellow condensed precipitate is formed that dissolves in methanol P. And with Bouchard at LP, a brown to black precipitate is formed. There is a possibility that an alkaloid is present (Zulkffle et al, 2014).…”
Section: Phytochemical Screening Test Alkaloid Identificationmentioning
confidence: 99%
“…These compounds form about 20% of plant based secondary metabolites and have long history in medication through their diverse pharmacological effects [43]. Zulkffle et al [53,54] identified alkaloid compounds in Tetrastigma tuberculatum using the phytochemical screening method and HPLC technique. It was shown that the radical scavenging activity of T. tuberculatum alkaloids is comparable to the standard reference, BHT but higher than the standard alpha tocopherol.…”
Section: Alkaloidsmentioning
confidence: 99%